Snakebite poisoning: A neglected disease - Matos,Bárbara Barroso De (2024)
Abstract Snakebite is a rare but potentially fatal cause of poisoning in children worldwide. It is a neglected public health issue in Europe, mainly affecting farmers and children, the latter suffering more severe consequences due to their small body mass. If poisoning is suspected, hospitalization of these patients is mandatory for clinical monitoring and early initiation of therapy. Snakebite can be a medical emergency. However, unlike many other serious health conditions, there is a highly effective treatment - anti-ophidian serum. It is crucial to invest in more effective and safer serums and to make them easily accessible in the event of a snakebite. The case of an adolescent affected by viper bite, its treatment and clinical course is reported.